Formulation of metronidazole tablets using hydroxypropylated white yam (dioscorea rotundata) starch as the binding agent (2017)
White yam starch obtained from the tubers of Dioscorea rotundata Poir was modified by hydroxypropylation and used as a binding agent in a metronidazole tablet formulation and compared with corn starch BP. The quantitative effects of the novel starch binder on the mechanical (tensile strength and friability) and release properties (disintegration and dissolution times) of the metronidazole tablet was analyzed using a full 23 factorial experimental design. The individual and interaction effects of type of starch binder (X1), concentration of binder (X2) and relative density (X3) on tensile strength, friability, disintegration time and dissolution time (t90) were determined. The ranking of the coefficients was X3 > X2 > X1 on T, X1 > X3 > X2 on F and X3 > X1 > X2 on DT and t90 (time for 90% drug release) indicating that the formulation variables influence the properties of metronidazole tablets to varying degrees. This indicates that the type and concentration of starch binder as well as the compression pressure employed in table formulation need to be carefully selected to obtain tablets with the desired mechanical and drug release properties. Hydroxypropyl white yam starch could be more useful as a binder especially when tablets require high mechanical strength and faster drug release are desired.